Os tratados bilaterais de investimento dos BRICS com países africanos: Uma análise comparativa com o ACFI brasileiro - Ana Saggioro Garcia; Manu Misra; Daniel Lannes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This study aims to deepen the debate on Brazil's insertion in the international investment regime by conducting a comparative analysis between Brazil's Agreement on Cooperation and Facilitation of Investments (ACFI) and the bilateral investment treaties of the other BRICS countries with African countries. We begin with an overview of the political and economic relations between China, South Africa, Russia and India with African countries. Then, we discuss the insertion of each BRICS country in the international investment regime, and present the characteristics of the BIT models used with countries on the African continent. We carried out a quantitative research and a qualitative analysis of the agreements' texts to identify their main characteristics. Additionally, we present the performance of the four BRICS countries in the international arbitration system, and analyze the cases involving African countries and BRICS. At the end, we recall the main characteristics of the ACFIs, and do comparative analysis between the models used by the other BRICS countries, pointing out their differences and similarities. We conclude that, although the BRICS countries are pushing for reforms in the international investment regime and are critically opposed to traditional BITs, which are usually established by countries from the Global North, in relations with African countries, the four BRICS countries analyzed here use the traditional BIT model, reinforcing its rules and principles. In this sense, they end up reproducing treaties between asymmetric economies, which guarantee rights to foreign investors to the detriment of the public interest in areas that are fundamental to societies, such as the environment, health, labor, and macroeconomic stability. Only the ACFI brings a differentiated agreement model, but it has not yet been actually put into practice, to be tested, improved, or even questioned as to its necessity. In our analysis, Brazil has a way to go, and should seek to promote investments with African countries in a balanced way, ensuring that these investments effectively contribute to economic, social and environmental development of the parties involved.
Keywords: F53; F55; O55; K2; 330; BRICS; bilateral investment treaties; Africa; ACFI